Inter-ocular Suppression and Sensory Eye Dominance in Human Vision - Wang, Mengxin (2020)
Inter-ocular interactions are a crucial component of binocular vision, providing important insights into how the inputs from the two eyes are combined and compete with each other. This aspect was addressed in a series of psychophysical experiments by investigating inter-ocular suppression and sensory eye dominance in the normal visual system. Firstly, patterns of individual differences, and variations in sensory eye dominance, in terms of susceptibility to binocular rivalry (BR) and continuous flash suppression (CFS), were established in a representative sample of participants. The results indicate that there may be a common mechanism underpinning these inter-ocular suppression phenomena, whilst sensory eye dominance associated with depth of suppression may be task dependent. Furthermore, this thesis has also demonstrated the adjustment of sensory eye dominance following short periods of monocular deprivation/distortion in the adult visual system. Crucially, it has been shown that changes in sensory eye dominance resulted specifically from reduced inter-ocular suppression of the previously treated eye. Moreover, the present findings underscore a role of inter-ocular imbalance in the visual processing, arising from both low-level sensory input and higher-level processes, in altering subsequent sensory eye dominance. Taken together, the findings of this thesis imply that there is a mechanism that detects inter-ocular conflict, which in turn elicits inter-ocular inhibition that is sensitive to imbalance between the two eyes' processing. These findings have contributed new knowledge to the understanding of inter-ocular interactions, and placed important constraints on the models of binocular vision.